UNCERTAINTY IN THE PERT’S CRITICAL PATH - Naili, Mohamed; Naili, Makhlouf; Tari, Abdelkamel (MATTER: International Journal of Science and Technology, 2018)
In this paper, the problem of scheduling is addressed. Due to difficulties in scheduling projects, researchers and professionals have proposed a tremendous number of works aiming at finding the best method to accomplish this phase of any project, especially if the decision maker is facing the challenge of uncertain estimations. One of the most used families of techniques is discussed in this paper, namely the Fuzzy Program Evaluation and Review Technique techniques. This family of techniques is based mainly on using the classical Program Evaluation and Review Technique and the fuzzy set theory. This work presents a comparison between two interesting techniques used to tackle the problem of uncertainty, namely the Model for Project Scheduling with Fuzzy Precedence Links and the Centroid techniques. The first technique is based on the relationship strength between each two activities in order to resolve the problem of the critical path. The second technique is based on a very simple mathematical concept and arithmetic of fuzzy numbers to tackle the same problem. Based on the results of a numerical example, we noticed that the simplicity and inexpensiveness of the Centroid method beat the complicated and expensive characteristics of the Model for Project Scheduling with Fuzzy Precedence Links.